Tea Tree Essential Oil Kills Escherichia coli and Staphylococcus epidermidis Persisters - LeeAnn Nguyen; Brianna DeVico; Maliha Mannan; Matthew Chang; Cristina Rada Santacruz; Christopher Siragusa; Sydney Everhart; Christopher H. Fazen (Biomolecules, 2023)
Persister cells are a small subpopulation of non-growing bacteria within a population that can survive long exposures to antibiotic treatment. Following antibiotic removal, persister cells can regrow and populate, playing a key role in the chronic reoccurrence of bacterial infections. The development of new molecules and methods to kill bacterial persisters is critical. Essential oils and other natural products have long been studied for their antimicrobial effects. Here, we studied the effectiveness of tea tree essential oil (TTO), a common component in many commercial care products, against Escherichia coli and Staphylococcus epidermidis persister cells. Using biphasic kill curve assays, we found that concentrations of 0.5% and 1.0% TTO for E. coli and S. epidermidis, respectively, completely eradicated persister cells over a period of 24 h, with the component terpinen-4-ol responsible for most of the killing. Using a colorimetric assay, it was determined that the TTO exhibited its anti-persister effects through a membrane disruption mechanism.